Предмет: Математика,
автор: oksana184
a-a^2+b+b^2 Помогите решить
Ответы
Автор ответа:
0
если правильно поняла тебе надо упростить способом группировки
а-а²+b+b²=(a+b)-(a²-b²)=(a+b)-(a-b)(a+b)=(a+b)(1-a+b)
а-а²+b+b²=(a+b)-(a²-b²)=(a+b)-(a-b)(a+b)=(a+b)(1-a+b)
Автор ответа:
0
спасибо)
Похожие вопросы
Предмет: Физика,
автор: treshalinamari87
Предмет: Математика,
автор: deadpoolpandapool
Предмет: Русский язык,
автор: Аноним
Предмет: Алгебра,
автор: KapitanKakao31
Предмет: Математика,
автор: elena8411984